The influence of online anime towards children - Abd Rahim, Normaliza; Sujud, Arbaie; Abdul Halim, Hazlina; Mamat, Roslina; Roslan, Siti Nur Aliaa (Online Journal of Communication and Media Technologies, 2013)
Online anime has been a major influence towards the growth of children in Malaysia. Therefore this study investigates the online anime that influence children in their everyday lives. The study also discusses the influence of online anime that contributed to positive interaction in the discussion between the children. The study involves 10 nine year olds subjects from a class of one school in Putrajaya. The children were selected based on their experience in watching online anime. The subjects were interviewed. They were in groups of 3 to 4. They discussed about the characters, setting and storylines from the online anime that they had watched and the conversation were taped and analyzed. Selected extracts were analysed and discussed by using the discourse analysis method. It is found that subjects were strongly influenced by the characters, setting and storylines from the online anime. They were happy and contented to be like the characters in the story. It is hoped that online anime were able to give positive influence towards children in their everyday lives.